Assessment of genetic variation for herbicide tolerance in sesame (Sesamum indicum L.) germplasm: ASSESSMENT OF GENETIC VARIATION FOR HERBICIDE TOLERANCE IN SESAME GERMPLASM - S GEETHANJALI,; BHAGYASHREE DEVRAO DURGE,; R SASIKALA,; N THAVAPRAKAASH,; M DHANDAPANI, (Journal of Oilseeds Research, 2022)
To assess genetic variation for herbicide tolerance in sesame, a set of 55 genotypes were sprayed with imazethapyr@75g ai/ha on the 18th day after sowing at seedling stage. A control plot without herbicide spray was maintained. The injury caused due to Imazethapyr spray was recorded visually on 1-5 scale and the survival rate was calculated on 7th, 10th, 13thand 15th day after treatment. The herbicide injury rating ranged from 2-4.8 on 7thday after herbicide spray (DAHS) and 3.7 -5.0 on the 15th DAHS. The survival rate progressively decreased from 7th DAHS to 15th DAHS inmost genotypes. The genotype, NIC-8261 was the most sensitive genotype expressing the symptoms of herbicide injury at a very early stage. On the 15th DAHS, only 10 genotypes viz., CO-1, OTS-2, SI-328, SI-3171, NIC-16106, G-53, SI-1769, TC-25, RT-146 and NIC-8317 had a survival rate ranging from27% to 39%. The subset of 10 genotypes was further evaluated for growth and yield attributes to assess the effect of imazethapyr spray on them. Imazethapyr spray resulted in delayed flowering and adversely caused a reduction in plant height, number of capsules per plant, seeds per capsule, thousand seed weight and seed yield per plant in the sesame genotypes. The findings of the study indicated that Imazethapyr@75gai/ha applied as a post-emergence herbicide at seedling stage was toxic to sesame and caused adverse effects on sesame growth and yield, by reducing the plant height, capsule production, thousand seed weight and also caused a delay in flowering. The response of sesame genotypes to Imazethapyr application was variable suggesting that genetic variability exists for herbicide tolerance in the germplasm, which need to be studied intensively.